Discovering Religious Pluralism in Islamic Tradition: An Effort to Gain Understanding of Others - Azeez, Ismail Adaramola Abdul; Afifuddin, Muhammad (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2023)
This article examines the role that devout multiplicity and municipal rights played by Prophet Muhammad’s (PBUH) for extending a multicultural society in which residency and equal rights were granted to all people irrespective of devout principles and practices. The Pacts of the Prophet Muhammad (PBUH) with the Christian relation of his time are used as a framework for reviving the democratic spirit of the covenants by transferring sympathetic religious freedom and municipal rights, which can lead to peaceful co-existence society. The pacts of Prophet Muhammad (PBUH) with the Christians of his time can be used to develop a stronger narrative of democratic partnership between Muslims and Christians and others in the global world and beyond. Prophet Muhammad recognizes diversity religious and cultural differences and engages in them in order to gain a sound understanding of the values and commitments of the different other.